Clinical and epidemiological characteristics of patients with Guillain Barré syndrome diagnosis attended in the physical medicine and rehabilitation service in the year 2019 - Burga-Bravo, Anaís De Faatima (2020)
Introduction: The Regional Health Management in Lambayeque, launches in 2019 the epidemiological alert on immediate notification of Guillain Barré cases, against the increase in confirmed cases and suspected cases of the disease Objective: Describe the clinical and epidemiological characteristics of patients with diagnosis Guillain Barré Syndrome treated in external medical consultation at the Physical Medicine and Rehabilitation Service of the Almanzor Aguinaga Asenjo National Hospital, during the outbreaks of the year 2019. Materials and methods: Descriptive, retrospective study. There were 48 cases registered in the Epidemiology database, 25 were evaluated in External Consultation in the Physical Medicine and Rehabilitation Service; 1 case per pregnancy was excluded. Results: Of the 24 cases evaluated; 14 (58.3%) were female and 10 (41.7%) male. The age group with the highest presentation was an adult with 12 cases (50%), followed by an older adult 6 (25%). The place of origin was Lambayeque, 16 (66.7%); Cajamarca 7 (29.2%) and La Libertad; 1 (4.2%). The presentation was ascending with 15 cases (62.5%) and descending with 9 (37.5%). 6 patients (25%) failed to march; 3 (12.5%) achieved a march with support and 15 (62.5%) achieved an independent march. Only 1 case (4.17%) presented cranial nerve involvement. Areflexia was found in 13 patients (54.2%). No patient arrived with muscle strength on a scale of 0 to 1 in both upper and lower limbs, proximal and distal. Conclusions: The study shows epidemiological and clinical characteristics of importance to project objectives and goals of rehabilitative treatment.